Molecular genetics of cytoplasmic male sterility and restorer-of-fertility for the fine tuning of pollen production in crops - Kitazaki, Kazuyoshi; Oda, Kotoko; Akazawa, Akiho; Iwahori, Ryoma (Theoretical and applied genetics, 2023)
Cytoplasmic male sterility (CMS) is an increasingly important issue within the context of hybrid seed production. Its genetic framework is simple: S-cytoplasm for male sterility induction and dominant allele of the restorer-of-fertility gene ( Rf ) for suppression of S. However, breeders sometimes encounter a phenotype of CMS plants too complex to be explained via this simple model. The molecular basis of CMS provides clue to the mechanisms that underlie the expression of CMS. Mitochondria have been associated with S, and several unique ORFs to S-mitochondria are thought to be responsible for the induction of male sterility in various crops. Their functions are still the subject of debate, but they have been hypothesized to emit elements that trigger sterility. Rf suppresses the action of S by various mechanisms. Some Rf s, including those that encode the pentatricopeptide repeat (PPR) protein and other proteins, are now considered members of unique gene families that are specific to certain lineages. Additionally, they are thought to be complex loci in which several genes in a haplotype simultaneously counteract an S-cytoplasm and differences in the suite of genes in a haplotype can lead to multiple allelism including strong and weak Rf at phenotypic level. The stability of CMS is influenced by factors such as the environment, cytoplasm, and genetic background; the interaction of these factors is also important. In contrast, unstable CMS becomes inducible CMS if its expression can be controlled. CMS becomes environmentally sensitive in a genotype-dependent manner, suggesting the feasibility of controlling the expression of CMS.